Enhancing Civil Servant Discipline through Modern Management Approaches - Radityan Aufaadaffa Andiraputra; Azharisman Rozie; Tunggul Prasodjo (Journal of Research in Social Science and Humanities, 2024)
The existence of regulations regarding civil servant discipline mandates that these employees exhibit high levels of discipline to deliver exceptional service, thereby fulfilling the government's objective of forming Civil Servants who serve society effectively. This study aims to examine the implementation of civil servant discipline, identify the inhibiting factors, and explore efforts to overcome obstacles in enforcing discipline among civil servants at the Samarinda City Personnel and Human Resources Development Agency Office. The research employs a qualitative approach with descriptive methods, utilizing both primary and secondary data sources. Data collection techniques include observation, interviews, and documentation. The theoretical framework is based on Hasibuan's theory of employee discipline indicators. The findings reveal that civil servant discipline at BKPSDM Samarinda City, based on the Discipline Indicator Theory, is generally good. However, several issues hinder the implementation of discipline, such as the long distance to the office, which affects mobility and time efficiency, and personality factors of undisciplined employees, who often misuse time after checking in and develop habits that are hard to change. Additionally, there is a lack of understanding among some employees regarding disciplinary regulations. Efforts to address these challenges include persuasive and firm reminders according to civil servant discipline rules, strict sanctions for rule violations, and dissemination of the latest disciplinary regulations to ensure understanding. The author suggests that BKPSDM Samarinda City should provide rewards for outstanding employees, address obstacles to discipline implementation more comprehensively, and be more explicit in sanctioning rule violations.